The Recovery of Thyroid Function in Low-Risk Papillary Thyroid Cancer After Lobectomy: A 3-Year Follow-Up Study - Dou, Yi; Chen, Yingji; Hu, Daixing; Su, Xinliang (Frontiers in Endocrinology, 2021)
Purpose: Management strategies after lobectomy for low-risk papillary thyroid carcinoma (PTC) are controversial. This study aimed to identify the proportion of patients among low-risk PTC patients who do not require hormone replacement therapy and to evaluate the risk factors for postoperative hypothyroidism after lobectomy. Patients and Methods: The records of 190 PTC patients who underwent thyroid lobectomy from January 2017 to December 2018 were retrospectively reviewed. Clinicopathological characteristics and follow-up data were collected. Univariate and multivariate analyses were performed to identify the risk factors associated with postoperative hypothyroidism and the recovery of thyroid function. Results: In summary, 74.21% of patients (141/190) had normal thyroid function without levothyroxine supplementation, while 40.53% (77/190) developed temporary or permanent hypothyroidism. Multivariate analysis indicated that higher preoperative thyroid-stimulating hormone (TSH) levels (>2.62 mIU/L), Hashimoto’s thyroiditis (HT), and right lobectomy were associated with hypothyroidism (all P<0.05). The AUC by logistic analysis was 0.829. Twenty-eight (28/77, 36.4%) patients recovered to the euthyroid state in the first year after surgery, and this recovery was significantly associated with preoperative TSH level. Forty-nine (49/77, 63.6%) patients developed persistent hypothyroidism. The thyroid function of most patients (11/28, 39.3%) recovered in the third month after surgery. Conclusion: Patients with a lower level of preoperative TSH, with left lobectomy and without Hashimoto’s thyroiditis had a higher chance of normal thyroid function within the first year after lobectomy. The recovery of thyroid function was associated with the level of preoperative TSH.